PCR Duplication: A One-Step Cloning-Free Method to Generate Duplicated Chromosomal Loci and Interference-Free Expression Reporters in Yeast. - Florian Huber (PLoS ONE, 2014)
Here, we report on a novel PCR targeting-based strategy called 'PCR duplication' that enables targeted duplications of genomic regions in the yeast genome using a simple PCR-based approach. To demonstrate its application we first duplicated the promoter of the FAR1 gene in yeast and simultaneously inserted a GFP downstream of it. This created a reporter for promoter activity while leaving the FAR1 gene fully intact. In another experiment, we used PCR duplication to increase the dosage of a gene in a discrete manner, from 1× to 2x. Using TUB4, the gene encoding for the yeast γ-tubulin, we validated that this led to corresponding increases in the levels of mRNA and protein. PCR duplication is an easy one-step procedure that can be adapted in different ways to permit rapid, disturbance-free investigation of various genomic regulatory elements without the need for ex vivo cloning.